Risk Factor and Surgical Outcome of Petersen’s Hernia After Gastrectomy in Gastric Cancer - Liu, Song; Hu, Qiongyuan; Song, Peng; Tao, Liang; Ai, Shichao; Miao, Ji; Wang, Feng; Kang, Xing; Shen, Xiaofei; Sun, Feng; Xia, Xuefeng; Wang, Meng; et al. (Frontiers in Oncology, 2021)
Background Petersen’s hernia is a life-threatening complication after gastrectomy. This study is dedicated to identify risk factors for Petersen’s hernia, and compare clinical outcome between patients receiving early or delayed surgical interventions. Methods All patients that received gastrectomy due to gastric cancer were collected. Clinical characteristics were compared between Petersen and non-Petersen groups, bowel necrosis and non-necrotic groups. Propensity score matching (PSM) was conducted to generate two comparative groups. Univariate analysis and multivariate Logistic regression were performed for risk factor evaluation. Results A total of 24 cases of Petersen’s hernia were identified from 1481 cases of gastrectomy. PSM demonstrated that lower BMI (OR=0.2, p<0.01) and distal gastrectomy (OR=6.2, p=0.011) were risk factors for Petersen’s hernia. Longer time interval from emergence visit to laparotomy (p=0.042), elevated preoperative procalcitonin (p=0.033) and CRP (p=0.012) were associated with higher risk of bowel necrosis in Petersen’s hernia. Early surgical intervention resulted in less bowel necrosis rate (p=0.012) and shorter length of necrotic bowel (p=0.0041). Conclusions Low BMI and distal gastrectomy are independent risk factor for Petersen’s hernia after gastrectomy. Curtailing observing time and executing prompt surgery are associated with bowel viability and better outcome in patients with Petersen’s hernia.